Procedures to estimate fecundity of marine fish species in relation to their reproductive strategy - Murua, Hilario; Kraus, Gerd; Saborido-Rey, Fran; Witthames, Peter R.; Thorsen, Anders; Junquera, Susana (Northwest Atlantic Fisheries Organization, 2003)
22 páginas, 7 figuras, 3 tablas, 2 apéndices. Appraisal of reproductive strategy and fecundity is necessary to evaluate the reproductive potential of individual fish species. To estimate reproductive potential, one needs to consider a variety of attributes including onset of maturity, fecundity, atresia, duration of reproductive season, daily spawning behaviour and spawning fraction. In this contribution, we review several methods currently used to estimate fecundity of marine fishes collected in the field in relation to their reproductive strategy. The advantages and disadvantages of each method are provided. Requirements are given to appropriately sample gonadal tissue that will enable researchers to establish incidence of sexual maturity and estimate fecundity. Peer reviewed